Urinary Tract Infection due to Extended-Spectrum Beta-Lactamase Producing Organisms is a risk Factor for Acute Kidney Injury among Patients diagnosed with Diabetes Mellitus Type 2 - Naimat Ullah, Talal Ali, Obaid Ur Rahman, Sheeraz Ahmed, Muhammad Hamza, Muhammad Zain Noorani, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: UTI is one of the most prevalent bacterial infection in the adults. It is reported that the risk of ESBL-positive UTI are greater in the diabetic patients with the poor glycemic control. Acute kidney damage (AKI) and sepsis may complicate the cases of UTI. Objective: This study was carried out to find whether the UTI caused by Extended-Spectrum Beta-Lactamase Producing Organisms is a risk Factor for Acute Kidney Injury among Patients diagnosed with Diabetes Mellitus Type 2. Study design: It is a case control study conducted at the nephrology department of Al-Nafees medical college and hospital Islamabad for the duration of six months from January 2022 to June 2022. Material and Material: This study was conducted on 98 patients suffering from diabetes mellitus, included majority were female members (n=55) and there were (n=43) male. The patients who had proven UTI infection were consider as the subjects for this study from their culture testing. Results: The average age of patients was 57.5 years. The diabetes mellitus mean duration was 8.77±5.77. It was seen that age, sex and duration of diabetes mellitus has no impact on the condition as no significant difference was seen. Conclusion: It was found that the UTI caused due to ESBL Producing Organisms like E. coli and K. pneumonia. The risk of developing UTI in diabetes mellitus type II is higher in case of ESBL producing organism infection. It is also a risk factor for acute kidney infection. Keywords: E. coli and acute kidney infection.